Sociolinguistic transfer in Japanese as a third language - Fouser, Robert Joseph (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2000)
This thesis explores the issue of language transfer in the acquisition of Japanese as a third or greater language at the university level. The term "L≥3" was adopted to describe the acquisition of a language or languages beyond a second language or first foreign language.
Keywords: Language and Communication Studies, Ph.D.; Ph.D. Trinity College Dublin